Mauritius : From Preferences to Global Competitiveness, Report of the Aid for Trade Mission - World Bank (Washington, DC, 2012)
Mauritius is facing a sharp transition from dependence on trade preferences to open competition in the global economy. And it must do so in an unusually difficult environment. After 20 years of remarkable performance, the economy has fallen off a high growth plateau of about 6 percent toward the 2-3 percent range. The creation of new jobs is now too slow to prevent an increase in unemployment. Domestic investment has fallen, the external accounts have shifted from surplus into deficit by $300 million, and the country has sporadically lost reserves. This report, the first step in a process, outlines the trade competitiveness challenges facing Mauritius that, if confronted and managed, will pave the way to a return to a higher growth path. After the Government develops the specific actions in its program, the Bank will work with the government in costing the specific investments necessary to implement its program of trade competitiveness, and will help in mobilizing external support as part of the international community's effort put together a global program of aid for trade.